Effects of various fractions of spray-dried plasma protein on performance of early-weaned pigs - K Q Owen; K G Friesen; B T Richert; J W Smith II; L E Russell; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1995)
Two experiments were conducted to determine the individual protein fraction (IgG, low molecular weight peptides and albumin) contained in spray-dried plasma protein responsible for stimulating feed intake. In Exp. 1, pigs (21 d of age) fed a diet containing the IgG protein fraction had similar performance to pigs fed a plasma protein diet. In Exp. 2, two fractions of spray-dried porcine plasma, IgG and albumin, were evaluated with pigs (10 d of age). Pigs fed either fraction had performance similar to pigs fed plasma protein.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Starter; Performance; Plasma protein